Lactobacillus acidophilus ameliorates H. pylori-induced gastric inflammation by inactivating the Smad7 and NFκB pathways - Yang, Yao-Jong (BioMed Central, 2012)
BACKGROUND: H. pylori infection may trigger Smad7 and NFκB expression in the stomach, whereas probiotics promote gastrointestinal health and improve intestinal inflammation caused by pathogens. This study examines if probiotics can improve H. pylori-induced gastric inflammation by inactivating the Smad7 and NFκB pathways. RESULTS: Challenge with H. pylori increased IL-8 and TNF-α expressions but not TGF-β1 in MKN45 cells. The RNA levels of Smad7 in AGS cells increased after H. pylori infection in a dose-dependent manner. A higher dose (MOI 100) of L. acidophilus pre-treatment attenuated the H. pylori-induced IL-8 expressions, but not TGF-β1. Such anti-inflammatory effect was mediated via increased cytoplasmic IκBα and depletion of nuclear NFκB. L. acidophilus also inhibited H. pylori-induced Smad7 transcription by inactivating the Jak1 and Stat1 pathways, which might activate the TGF-β1/Smad pathway. L. acidophilus pre-treatment ameliorated IFN-γ-induced Smad7 translation level and subsequently reduced nuclear NF-κB production, as detected by western blotting. CONCLUSIONS: H. pylori infection induces Smad7, NFκB, IL-8, and TNF-α production in vitro. Higher doses of L. acidophilus pre-treatment reduce H. pylori-induced inflammation through the inactivation of the Smad7 and NFκB pathways.